Immersive Audio Storytelling: Podcasting and Serial Documentary in the Digital Publishing Industry - Dowling, David O.; Miller, Kyle J. (Journal of radio & audio media, 2019)
Structural shifts behind the rise of podcasting have led to programming aimed at sustaining audience attention, a development coinciding with the sharp increase in engaged time with digital longform content among mobile users. This study industrially and culturally situates 3 case studies: True Murder (a pioneering precursor to This American Life producers' Serial), S-Town (Serial's successor that far exceeded its listenership), and Ear Hustle (Radiotopia's experiment in subject-produced content made by two inmates at San Quentin State Prison). Each case illustrates how distinct sectors of the podcasting industry approach the production of absorbing nonfiction through transparent journalism featuring self-reflexive metanarrative.